If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+5y=6+3y
We move all terms to the left:
2+5y-(6+3y)=0
We add all the numbers together, and all the variables
5y-(3y+6)+2=0
We get rid of parentheses
5y-3y-6+2=0
We add all the numbers together, and all the variables
2y-4=0
We move all terms containing y to the left, all other terms to the right
2y=4
y=4/2
y=2
| 2.5*p=7 | | 4x+563x+78+234=180 | | 4(2y)-8y=6 | | 4x-8(1.5)=6 | | x-35=-5 | | x^2(3x-4)(x-2)^3=0 | | 6·(–9)=9.5(a–6.9)2 | | x*1.5=11 | | xx1.5=11 | | (2)=-3x-3 | | 25+q=28 | | x÷12=-4 | | 16=0.5^2x | | 170=42x^2 | | 3x-8=2-1 | | S²+3s+2=0 | | 39=-7u+5(u+5) | | 2.4/6=z.5/8 | | 180=(x+3)^2+11 | | 40x+1.5x=83000 | | 30+30×0+a=1 | | 10x+35+x=180 | | 0.05x=x-3.99 | | x-23=-48 | | 3/x+2=19 | | 7x(2x-1)=35 | | (4-6x)×2=(8x+1) | | (4-6x)-41=(9x-3) | | (4-6x)-4+1=(9x×2) | | (4-6x)-4+1=(9x×2x) | | (3x-5)-3=(31+2x) | | (7x-2)+71=(8-1x) |